Better learning through structured teaching : a framework for the gradual release of responsibility - Fisher, Douglas, 1965-; Frey, Nancy, 1959- (ASCD, 2021)
"The definitive guide to the gradual release of responsibility-an instructional framework teachers can use to help students become more successful and self-directed learners"--